Integrating Qualitative Comparative Analysis (QCA) and Fuzzy Cognitive Maps (FCM) to Enhance the Selection of Independent Variables - Ferreira, F.; Jalali, M.; Ferreira, J. (2015 GIKA International Conference, 2015)
This study proposes the integrated use of fuzzy cognitive maps (FCMs) in qualitative comparative analysis (QCA) applications to enhance the selection of independent variables in the QCA framework. QCA techniques are often used to identify the causal models that exist among different but comparable cases. Due to the complexity of causality issues, however, such techniques may not be able to uncover the “true” causal foundation of a given phenomenon. FCMs, on the other hand, typically offer a fuller view of the cause-and-effect relationships between variables, thus allowing for a better understanding of their behavior; for instance, the manner in which variables relate to each other, or the measure of their intensity. This study thus proposes that such maps can be a useful support in the selection of independent variables for a QCA model; and provides specific guidelines and an illustrative example of how to integrate FCMs in QCA applications.